Spirituality and religiosity in a palliative medicine population: mixed-methods study. Issue 3 (4th June 2020) - O'Callaghan, Clare C; Georgousopoulou, Ekavi; Seah, Davinia; Clayton, Josephine M; Kissane, David; Michael, Natasha
Abstract : Background: Spiritual care allows palliative care patients to gain a sense of purpose, meaning and connectedness to the sacred or important while experiencing a serious illness. This study examined how Australian patients conceptualise their spirituality/religiosity, the associations between diagnosis and spiritual/religious activities, and views on the amount of spiritual support received. Methods: This mixed-methods study used anonymous semistructured questionnaires, which included the Functional Assessment of Chronic Illness Therapy-Spiritual Scale-12 (FACIT-SP-12) and adapted and developed questions examining religion/spirituality's role and support. Results: Participants numbered 261, with a 50.9% response rate. Sixty-two per cent were affiliated with Christianity and 24.2% with no religion. The mean total FACIT-SP-12 score was 31.9 (SD 8.6). Patients with Christian affiliation reported a higher total FACIT-SP-12 score compared with no religious affiliation (p=0.003). Those with Christian and Buddhist affiliations had higher faith subscale scores compared with those with no religious affiliation (p<0.001). Spirituality was very important to 39.9% and religiosity to 31.7% of patients, and unimportant to 30.6% and 39.5%, respectively. Following diagnosis, patients prayed (p<0.001) and meditated (p<0.001) more, seeking more time, strength and acceptance. Attendance at religious services decreased with frailty (p<0.001), while engagement in other religious activities increased (p=0.017). Patients who received some level of spiritual/religious support from external religious/faith communities and moderate to complete spiritual/religious needs met by the hospitals reported greater total FACIT-SP-12 spirituality scores (p<0.001). Conclusion: Respectful inquiry into patients spiritual/religious needs in hospitals allows for an attuned approach to addressing such care needs while considerately accommodating those disinterested in such support.